Mikroprintai ir jų panaudojimas bibliotekų darbe - Urbonas, Viktoras (Knygotyra, 1986)
Microprints appeared in 1949. Their production was started by the American firm Readex Microprint. In the course of 34 years this firm had published a great amount of different material by using this technique. Microprints are concentrated in libraries all over the world and are successfully used. The microprints produced by Readex Microprint are known in our country due to advertising and personal contacts. In Lithuania the microprints are being used by the scientific library of Vilnius University.The serial production of home-made microprints started in 1965 at an average of 2 mln. cards a year. The libraries were equipped with microprints, but nevertheless the serial production stopped.The microprints have certain superiority over other techniques, as well as certain shortcomings. It has to be understood that the microprints production with the need of them and with the readers requests.The production of microprints in Lithuania expedient to concentrate at the scientific library of Vilnius University, which has certain experience in this work.It is recommended to use the technical means of the firm Readex Microprints while working with the microprints.